The profile of prospective physics teachers' conceptual change based on cognitive style dimensions through collaborative learning on electricity and magnetism topic. Issue 1 (June 2021) - Rahmawati, R; Rustaman, N Y; Hamidah, I; Rusdiana, D
Abstract: This study aims to explore conceptual changes of prospective physics teachers on electricity and magnetism topic based on the different of their cognitive style dimension through collaborative learning. The research method used was pre-experiment with pre-test and post-test designs. The sample in this study was 30 prospective physics teachers at a university in Makassar for the first year of the 2018/2019 academic year. Conceptual changes of prospective physics teachers were measured by the four-tier test. The analysis of conceptual changes was divided into three categories, namely not understanding, understanding, and misconceptions. Cognitive style were divided into Field Independence (FI) and Field Dependence (FD) which were measured using the Group Embedded Figure Test (GEFT) standard test. The results showed that there were no FI students who had misconceptions both on the initial and final test but decreased in the category of not understanding (1%), and increased in the category of misconceptions (1%). Meanwhile, FD students experienced misconceptions both on the initial test (34%) and the final test (20%) but decreased in not understanding (2.7%) and increased in understanding (17.7%). The results also provided collaborative learning contributed to improve students' conceptual changes from misconceptions and not understanding concepts to be understanding concepts.